Serbia Country Economic Memorandum : Productivity and Exports - Sestovic, Lazar; Miovic, Peter (World Bank, Washington, DC, 2014)
In order to have both dynamic and better balanced growth, Serbia needs to rely more on exports. In the last decade, Serbia's growth has depended primarily on demand that was fueled by excessive debt finance. In the future, the Serbian economy would be better served by increasing its reliance on exports as a new, potentially powerful source of growth. Serbia's export share of Gross Domestic Product (GDP) is currently 25 percent, but that figure should be closer to 50-75 percent, considering that all European Union (EU) comparator countries1 have export shares of GDP of 60-80 percent. Some sectors of the economy are already better positioned than others to export. For example, sectors in the traditional export base of Serbia, such as food and some chemical products still have vast potential for growth. Agriculture is widely considered to have significant potential for improvement. Although Serbia has recently become a net food exporter, these exports could be substantially higher. The Serbian government's number one task is to accelerate reforms to create an environment that is highly conducive to export-led growth. Serbia will need to fundamentally alter its growth model in order to compete effectively in world markets. The past model of relying on excessive inflows of capital and credit coupled with a consumption boom has run its course in all European countries, including Serbia.